INTELLECTUAL CAPITAL DAN KINERJA SOSIAL PERBANKAN SYARIAH DI INDONESIA: SEBUAH KAJIAN KONSEP DAN EMPIRIS - SUHENDA WIRANATA; ALI RAMA (Universitas Islam Negeri Imam Bonjol Padang, 2018)
The study aims to examine the influence of intellectual capital to social performance of Islamic banks. The study assumes there is an intervening role of financial performance on the relation between intellectual capital and social performance of Islamic banks. The VAIC (valued added intellectual capital) is used to measure the intellectual capital. While social capital of Islamic banks comprises four main aspects which are contribution economic development, society, stakeholders, and human development & research. The financial performance is represented by ROA and ROE. The study finds that intellectual capital of Islamic banks has an increasing performance during the period of the study where human capital is the main backbone. Otherwise, social performances of Islamic banks are relatively fluctuated and tend to remain stable during the period. The statistical test shows that intellectual capital has no significant impact on social performance of Islamic banks. However intellectual capital positively and significantly influences financial performance of Islamic banks.